Leaf flavonoid content in Quercus ilex L. resprouts and its seasonal variation - Brossa, R.; Casals, I.; Pintó-Marijuan, M.; Fleck, I. (Trees, 2008)
Here, we provide the ﬁrst report on ﬂavonoid content in holm oak (Quercus ilex L.) leaves, analyzed by HPLC–MS/MS. Flavanols and ﬂavonols were the predominant groups, although proanthocyanidins and many soluble tannins had a relevant presence in all leaf samples. Seasonal variation of ﬂavonoids was determined in extracts from Q. ilex leaves during resprouting after a forest ﬁre in two Mediterranean forests. Similar seasonal trends were observed over 2 years during the two main stress seasons (winter and summer). The most abundant ﬂavonoid was the ﬂavanol epicatechin, which showed similar values during the two seasons. Hexosides of the ﬂavonols, quercetin, kaempferol and rhamnetin showed considerably higher content in winter, especially at the lowest temperatures. These variations in both forests are discussed on the basis of the chlorophyll ﬂuorescence results obtained. Anthocyanins were found practically absent in mature leaves. Nutrient or water availability differences between sites or seasons were not related to changes in leaf ﬂavonolhexoside content.
Keywords: á; á hplc; chlorophyll fluorescence; chlorophyll fluorescence á flavanols; esi; flavanols; flavonol-hexosides; flavonol-hexosides á holm oak; Holm oak; HPLC–ESI–MS/MS; ms

Leaf flavonoid content in Quercus ilex L. resprouts and its seasonal variation - Brossa, R.; Casals, I.; Pintó-Marijuan, M.; Fleck, I. (Trees, 2008)
Here, we provide the ﬁrst report on ﬂavonoid content in holm oak (Quercus ilex L.) leaves, analyzed by HPLC–MS/MS. Flavanols and ﬂavonols were the predominant groups, although proanthocyanidins and many soluble tannins had a relevant presence in all leaf samples. Seasonal variation of ﬂavonoids was determined in extracts from Q. ilex leaves during resprouting after a forest ﬁre in two Mediterranean forests. Similar seasonal trends were observed over 2 years during the two main stress seasons (winter and summer). The most abundant ﬂavonoid was the ﬂavanol epicatechin, which showed similar values during the two seasons. Hexosides of the ﬂavonols, quercetin, kaempferol and rhamnetin showed considerably higher content in winter, especially at the lowest temperatures. These variations in both forests are discussed on the basis of the chlorophyll ﬂuorescence results obtained. Anthocyanins were found practically absent in mature leaves. Nutrient or water availability differences between sites or seasons were not related to changes in leaf ﬂavonolhexoside content.
Keywords: á; á hplc; chlorophyll fluorescence; chlorophyll fluorescence á flavanols; esi; flavanols; flavonol-hexosides; flavonol-hexosides á holm oak; Holm oak; HPLC–ESI–MS/MS; ms

Variations in Quercus ilex chloroplast pigment content during summer stress: involvement in photoprotection according to principal component analysis - Llorens, L.; Aranda, X.; Abadia, A.; Fleck, I. (FUNCTIONAL PLANT BIOLOGY, 2002)
We examined chloroplast pigment variation in holm oak (Quercus ilex L.) leaves for two periods under two climatic conditions, at midday during summer. We compared variation between control (unburned) plants and plants burned the preceding summer, since post-fire resprouts show higher photosynthetic rates and lower thermal energy dissipation. Principal component (PC) analysis was performed on nine pigment-content variables for the two periods separately. Two PC factors (PC1 and PC2) explained 83 and 84% of the variance of the data for each period. In both periods, PC 1 was marked by positive loading of pigments associated with light absorption or structural function namely neoxanthin, lutein, beta-carotene, chlorophyll a, and chlorophyll b. These pigments were only affected by leaf age. In contrast, PC2 was marked by high loadings of xanthophyll-cycle pigments (associated with photoprotection), and lutein-5,6-epoxide. Leaf content of these pigments was affected by climatic conditions. In the situations considered in PC analysis (leaf types, periods), the lutein-5,6-epoxide content presented a variation pattern similar to that of violaxanthin, and was significantly correlated with thermal dissipation of excess energy (represented by non-photochemical quenching or NPQ). These results suggest a relationship of lutein and lutein-5,6-epoxide with photoprotection.
The following values have no corresponding Zotero field: pub-location: 150 OXFORD ST, PO BOX 1139, COLLINGWOOD, VICTORIA 3066, AUSTRALIA publisher: C S I R O PUBLISHING
Keywords: 6-epoxide; chlorophyll; lutein-5; photoprotection; Principal component analysis

Light energy dissipation in Quercus ilex resprouts after fire - Fleck, I.; Aranda, X.; El Omari, B.; Permanyer, J.; Abadia, A.; Hogan, K. P. (AUSTRALIAN JOURNAL OF PLANT PHYSIOLOGY, 2000)
Holm oak (Quercus ilex) plants that have resprouted after fire have higher photosynthetic capacity than control plants in intact vegetation. In this study, branches detached from forest plants were fed with dithiothreitol (DTT) in the laboratory to inhibit zeaxanthin production and thus reduce the dissipation of light energy as heat. This allowed us to test the hypothesis that plants with greater photosynthetic capacity, and therefore greater photochemical sink strength, would suffer a lower reduction in photochemical efficiency under stressful conditions. Greater rates of photochemistry in resprouts, which exhibited increased photosynthesis (A), leaf conductance (g), quantum yield of PSII (Delta F/F-m') and photochemical quenching (q(P)), were related to lower non-radiative dissipation of excess energy as indicated by 1 - (F-v'/F-m'). However, the fraction of energy remaining of that used in photochemistry or dissipated thermally in the PSII antennae was similar in resprouts and controls and was not affected by DTT, especially under high irradiance conditions. Zeaxanthin involvement in PSII protection operated in resprouts and controls since DTT induced the same kind of response (NPQ decrease) but was lower in resprouts. These chlorophyll fluorescence results suggest the participation of some additional mechanism for energy dissipation. Light capture characteristics of the photosynthetic apparatus did not differ between resprouts and controls, and leaf age did not play a determining role in the differences observed.
APSAPSThe following values have no corresponding Zotero field: pub-location: 150 OXFORD ST, PO BOX 1139, COLLINGWOOD, VICTORIA 3066, AUSTRALIA publisher: C S I R O PUBLISHING
Keywords: DTT; photochemical sink; Quercus ilex

Quercus ilex resprouts after fire: response to photoinhibition. - Aranda, X.; Hogan, K.; Llorens, L.; Fleck, I. (PLANT PHYSIOLOGY, 1997)
The study was located on Serra del Garraf mountains, Barcelona, NE Spain, overlooking the Mediterranian sea at 530 m. On August 1995 a wild fire consumed 100 hectares of the forest. In spring 1996 four plots were set (100 x
APSAPSThe following values have no corresponding Zotero field: pub-location: 15501 MONONA DRIVE, ROCKVILLE, MD 20855 publisher: AMER SOC PLANT PHYSIOLOGISTS
Keywords: Mediterranean; wild fire

Influence of fire and tree-fell on physiological parameters in Quercus ilex resprouts - Fleck, I.; Grau, D.; Sanjose, M.; Vidal, D. (Ann. For. Sci., 1996)
Variations in the physiology of two kinds of resprout (originated after fire and after tree-fell) of Quercus ilex were analyzed under field conditions and compared with respect to the original, undisturbed vegetation, located within a Mediterranean watershed (northeast Spain). Resprouting vegetation of Quercus ilex after fire or after tree-fell showed, during the next growing seasons, enhanced photosynthesis, leaf conductance and Rubisco activity with respect to the original vegetation, especially under high temperature, irradiance and vapor pressure deficit (VPD). The lack of differences in nutrient (N,C,P,K and Ca) and soluble carbohydrate concentrations in leaves of resprouts originated after fire or after tree-fell indicates the independence of nutrients released by the action of fire and the contribution of underground organs. Differences in leaf mass per area (LMA) were due to increased thickness in resprouts whereas density was the same. N investment in chlorophylls or Rubisco was not different in control or either kind of resprout. The increased amount of carotenoids in resprouts contributed to providing protection from photoinhibitory processes
Keywords: fire; Gas exchange; Nutrients; photosynthetic pigments; Quercus ilex; tree-fell